2003
DOI: 10.1007/s00415-003-1073-5
|View full text |Cite
|
Sign up to set email alerts
|

Short latency trigemino-sternocleidomastoid response in patients with migraine

Abstract: Our findings further support and emphasise the role of the trigeminal system in the pathogenesis of migraine. The bilateral location of the abnormalities suggests a centrally located dysfunction. Therefore, the trigemino-cervical reflex is sensitive in disclosing a disturbed brainstem activity and may be an index of neuronal activity in the human brainstem; moreover their assessment may help as valuable prognostic tool for predicting the efficacy of triptans therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…Similar results were obtained in our previous study in different patient groups with headache [15]. Our findings confirmed the data reported by Nardone et al [16,17], who found abnormalities in latency and amplitude of the response in patients with migraine [16] and in patients with chronic tensiontype headache [17].…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were obtained in our previous study in different patient groups with headache [15]. Our findings confirmed the data reported by Nardone et al [16,17], who found abnormalities in latency and amplitude of the response in patients with migraine [16] and in patients with chronic tensiontype headache [17].…”
Section: Discussionsupporting
confidence: 93%
“…The results of the controls were similar to those previously reported studies [9, 1114]. However, the effect of hormonal change on with neurophysiologic studies of trigeminal system of controls has not been studied extensively so far.…”
Section: Discussionsupporting
confidence: 89%
“…Milano et al [12] studied long latency of TCR of migraine patients during headache-free period and found that the mean onset TCR after ipsi- and contralateral stimulation was significantly shortened on the painful side of migraine patients ( P  < 0.01). Recently, the recovery curve of the TCR was found to be significantly faster in migraine patients than in controls, suggesting that the pain-free period in migraine patients was characterized by a hyperexcitability of the trigeminal pathways [14]. In our study, the long latency of TCR was of shortened latency in all patients with headache during the perimenstrual period, compared with headache-free and the controls ( P  < 0.01).…”
Section: Discussionsupporting
confidence: 53%
“…Two separate groups found reduced latencies of the trigemonocervical reflex in patients with chronic TTH [129-131]. Using a nociception-specific electrode lower values of the normalized root mean square and area under the curve of the blink with control subjects [132].…”
Section: Reviewmentioning
confidence: 99%